THE PROSPECTS FOR ATTRACTING INVESTMENTS IN PORTS OF UKRAINE - С. А. Горбаченко (Ринкова економіка: сучасна теорія і практика управління)
In the article the investment component of seaports Ukraine is considered. The dependence of the seaports of investment resources is too high. At the same time the effectiveness of investment projects in certain ports are very different. The most attractive for investments are Great ports of Odesa; the ports of Azov are the least attractive.  Through the implementation of investment projects it is possible to ensure the sustainable development of ports not only directly, but also by means of other marine companies from shipbuilding and ship repairing enterprises to crewing companies. The current situation in the port sector in terms of its competitiveness is analyzed. Factors influencing the pace of attracting investment in the port sector are viewed. Successful implementation of projects in the ports is associated not only with industry but also with the local level of factors connected with the features of each individual port. The list of the aforementioned factors is very wide: from hydrographic changes in water area depending on the level of activity of the port to the local authorities and large financial-industrial groups. In the article reforms of the port sector and implementing innovative partnership arrangements with private investors are proposed. The main features of the project activity in the port area are formulated.